Meningkatkan Keterampilan Menjahit Celana Kulot melalui Model Pembelajaran Explicit Instruction Peserta Didik Kelas XI Hambatan Pendengaran - Sepdiah, Sepdiah; Ardisal; Elsa Efrina; Setia Budi; Rila Muspita (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to improve the skill of sewing culottes for eleventh-grade students with hearing impairments through the explicit instruction learning model. This research employs classroom action research (CAR) with a qualitative approach, conducted collaboratively between the researcher and the classroom teacher. The subject of the study was one eleventh-grade student with hearing impairment in class XI-B at SLB Muhammadiyah Pauh IX Padang. Data were collected using test instruments to assess the student's culotte sewing skills and non-test instruments, including observations, documentation, and interviews, to evaluate the student's responses to the learning process. The research was carried out in two cycles, each consisting of four stages: planning, action, observation, and reflection. Data analysis involved descriptive statistics for quantitative data presented as sewing skill percentages, and Miles and Huberman's qualitative analysis consisting of data reduction, data display, and conclusion drawing. The results showed that the student’s initial average skill was 50.69%. After Cycle I, the average increased to 63.75%, and after Cycle II, it reached 82.08%. These findings indicate that the explicit instruction model, applied in a structured and step-by-step manner, effectively enhances the sewing skills of students with hearing impairments.